(untitled) (Dhaka University Journal of Biological Sciences, 2017)
Work on two freshwater Gobi fish species such as Awaous guamensis and A. grammepomus was carried out on morphometric and meristic study for their morphological identification. Sequence data of mitochondrial cytochrome oxidase subunit I (COI) gene was used for this purpose. Around 620 bp sequences were obtained when universal primers were used. An alignment was performed between the sequences which showed some inter-specific variation. An entropy plot was generated for all the aligned positions which showed that the entropy rarely touches a scale of one, which is a sign of better alignment in the region. This work can be utilized for species identification, phylogenetic analysis, to study molecular diversity and evolution, and most importantly for the conservation of these fauna in near future. Dhaka Univ. J. Biol. Sci. 26(1): 83-90, 2017 (January)